A COMPREHENSIVE OVERVIEW ON AGNI - R.L.D.S, Ranasinghe; E.R.H.S.S, Ediriweera (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda, the science of life is based on several concepts. Concept of Agni is one of them. This study aims to explore the knowledge on Agni and mainly based on the authentic Ayurveda texts. Ayurveda has given prime importance to Agni (digestive fire) as it is one of the basic biologic elements of the living body. Agni has its own physical characteristics, location and functions in the body. Ayurveda emphasized that the balance state of Agni is essential to maintain the health of an individual. If Agni devoid of its normal functions it will leads to diseases. Different views have been suggested regarding Pitta and Agni by different Acharyas. Some Acharyas consider Pitta to be Agni while others speak Pitta is different from Agni. Although different types of Agnis are described in Ayurveda, thirteen types of Agnis viz 7 Dhatvagnis, 5 Bhutagnis and 1 Jatharagni are mostly considered. Jatharagni is also classified into four categories according to its performance of digestion in the human being namely Vishamagni, Teekshanagni, Mandagni and Samagni. Agni converts food in the form of energy, which is responsible for all the vital functions of our body.